Customer Relationship Management and Its Effects on Performance in the Hospitality Sector - Mirakhor, Abbas (Journal of Policy Options, 2021)
Customer Relationship Management (CRM) is gaining increasing attention and is emerging as one of the most significant topics in both academic research and business practice. With the growing competitiveness across industries, CRM has become a critical tool for enhancing firm performance, allowing companies to build stronger relationships with customers and tailor their services to meet evolving needs. In particular, CRM helps firms to differentiate themselves in highly competitive markets by offering personalized experiences and fostering customer loyalty. Despite its recognized importance, research examining the direct relationship between CRM dimensions and organizational performance, particularly in the hotel industry, remains limited. Given the service-oriented nature of the hospitality sector, understanding how different CRM components—such as customer engagement, data management, service customization, and communication strategies—affect hotel performance could provide valuable insights. Exploring this relationship could uncover how CRM practices improve guest satisfaction, increase repeat visits, and ultimately enhance the overall performance and profitability of hotels. Expanding research in this area is crucial for determining the specific CRM strategies that most effectively contribute to success in the hotel industry. This study aims to develop a valuable conceptual model that elucidates the theoretical connections between CRM dimensions and hotel performance. By exploring this relationship, the study seeks to provide a deeper understanding of how various CRM elements, such as customer engagement, data management, and service customization, directly influence hotel outcomes, including profitability, customer satisfaction, and brand loyalty. Additionally, the study goes beyond the direct relationship by examining the mediating role of marketing capabilities. Marketing capabilities, such as market sensing, customer relationship management, and product development, are crucial in translating CRM strategies into enhanced performance outcomes. The study will analyze how these capabilities bridge the gap between CRM initiatives and improved hotel performance, offering insights into the mechanisms through which CRM practices can be effectively leveraged for competitive advantage in the hospitality sector. This dual focus not only clarifies the relationship between CRM dimensions and hotel performance but also highlights the strategic importance of marketing capabilities in maximizing the benefits of CRM.